3-1 Beacon Hill Place, ca. 1860-89 - Unknown (Tufts Archival Research Center, 2005)
Street-level view west-northwest of (left to right) 3-1 Beacon Hill Place, located between Bowdoin Street to the east and Mount Vernon Street to the west. The facades of 1-3 Beacon Hill Place face south. Buildings lining the north side of Mount Vernon Street are visible in the center-left side of the photograph. Two boys stand on the sidewalk at the northwest corner of Bowdoin Street and Beacon Hill Place, and street lights line the sidewalk along Mount Vernon Street. Copyprint. Written on the back of OSZ photograph is viewed from Swedenborgion (sp) Church steps 10 x 8 Photographs